1991
DOI: 10.1063/1.347586
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced effects with scanning force microscopy

Abstract: We present a general theory that describes the operation of scanning force microscopy in the contact force regime. We find that force derivatives along the surface of a sample produce images that can be dramatically enhanced relative to those of surface topography. For scanning tunneling microscopy atomic force microscopy (STM/AFM) and AFM configurations, the spring constant of the cantilever and the force derivatives perpendicular to the surface of the sample determine the enhancement, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In regions where it is small, usually far from the sample, an amplification of lateral forces was observed. This agrees with an earlier report about the influence of electrostatic forces when the cantilever spring constant is small (Howells et al, 1991). The spring constant applied in the present measurements was 0.37 N/m.…”
Section: Introductionsupporting
confidence: 94%
“…In regions where it is small, usually far from the sample, an amplification of lateral forces was observed. This agrees with an earlier report about the influence of electrostatic forces when the cantilever spring constant is small (Howells et al, 1991). The spring constant applied in the present measurements was 0.37 N/m.…”
Section: Introductionsupporting
confidence: 94%
“…In contact mode, the tip apex is in firm contact with the surface throughout the scan, while maintaining a set load. 81 In this case, topographic and lateral force images are acquired simultaneously for both trace and retrace scan directions. Note, the lowest imaging force should be used to avoid the compression of the SLB.…”
Section: ■ Primary Methods For the Preparation Of Solid-supported Bil...mentioning
confidence: 99%
“…Two raster scan imaging modes are primarily used to characterize the structure and morphology of SLBs: tapping and contact mode. , Contact mode with soft cantilevers typically yields high-resolution images for gel phases, while tapping mode is necessary for liquid phases or layers with hydrophilic termini, which tend to have high adhesion to Si and Si 3 N 4 AFM tips. In contact mode, the tip apex is in firm contact with the surface throughout the scan, while maintaining a set load . In this case, topographic and lateral force images are acquired simultaneously for both trace and retrace scan directions.…”
Section: Characterization Of Solid-supported Bilayersmentioning
confidence: 99%
“…One reason for this could be the size of the tip apex used for STM, which is smaller than for AFM, although no details were given on the apex of the STM tip that they used. It has been observed that the pyramidal form of the AFM tip increases the size of the protuberance scanned, 26 thus causing an overestimation of the size of the grain. Moreover, depending on the spatial frequency of the protuberance on the surface, some small hills that have a diameter smaller than the diameter of the tip apex cannot be scanned 27 and consequently, they are not taken into account for the calculation of D. On the other hand, the coherence scattering length, ␦, obtained by XRD underestimates the size of the crystallographic grains, since grain boundaries, defects in the grain, and stresses in the films reduce the coherent scattering depth.…”
Section: Resultsmentioning
confidence: 99%